Real and perceived employability: a comparison among Italian graduates. Issue 4 (3rd July 2016) - Caricati, Luca; Chiesa, Rita; Guglielmi, Dina; Mariani, Marco Giovanni
ABSTRACT: The research undertaken for this article aims to analyse the correspondence between perceived employability and the actual national employment rate among Italian students and graduates undertaking different courses in a large Italian university. Data were collected through a cross-sectional survey of 2087 students in 19 faculties, and compared with the national indicators of employment rate for each faculty. Using faculty as unit of analysis, the results indicated a significant correlation between participants' perceived employability and national employment rate. This trend was similar for both genders. However, the results showed a difference between bachelor's and master's degrees: the correlation between perceived and actual employability was not significant among bachelor's participants while it remained significant among master's participants. The results suggest that graduates are only partially aware of their possibility to enter the labour market and this, in turn, highlights that universities have only partially met the goal to increase awareness about the chances of finding a job among students and graduates.